Clinical significance of histological classification of idiopathic interstitial pneumonia - Flaherty, K.R; Toews, G.B; Travis, W.D; Colby, T.V; Kazerooni, E.A; Gross, B.H; Jain, A; Strawderman, R.L., III; Paine, R; Flint, A; Lynch, J.P., III; Martinez, F.J (The European respiratory journal, 2002)
Patients with idiopathic interstitial pneumonias (IIPs) can be subdivided into groups based on the histological appearance of lung tissue obtained by surgical biopsy. The quantitative impact of histological diagnosis, baseline factors and response to therapy on survival has not been evaluated. Surgical lung biopsy specimens from 168 patients with suspected IIP were reviewed according to the latest diagnostic criteria. The impact of baseline clinical, physiological, radiographic and histological features on survival was evaluated using Cox regression analysis. The predictive value of honeycombing on high-resolution computed tomography (HRCT) as a surrogate marker for usual interstitial pneumonia (UIP) was examined. The response to therapy and survival of 39 patients treated prospectively with high-dose prednisone was evaluated. The presence of UIP was the most important factor influencing mortality. The risk ratio of mortality when UIP was present was 28.46 (95% confidence interval (CI) 5.5–148.0; p=0.0001) after controlling for patient age, duration of symptoms, radiographic appearance, pulmonary physiology, smoking history and sex. Honeycombing on HRCT indicated the presence of UIP with a sensitivity of 90% and specificity of 86%. Patients with nonspecific interstitial pneumonia were more likely to respond or remain stable (9 of 10) compared to patients with UIP (14 of 29) after treatment with prednisone. Patients remaining stable had the best prognosis. The risk ratio of mortality for stable patients compared to nonresponders was 0.32 (95% CI 0.11–0.93; p=0.04) in all patients and 0.33 (95% CI 0.12–0.96; p=0.04) in patients with UIP. The histological diagnosis of usual interstitial pneumonia is the most important factor determining survival in patients with suspected idiopathic interstitial pneumonia. The presence of honeycombing on high-resolution computed tomography is a good surrogate for usual interstitial pneumonia and could be utilized in patients unable to undergo surgical lung biopsy. Patients with nonspecific interstitial pneumonia are more likely to respond or remain stable following a course of prednisone. Patients remaining stable following prednisone therapy have the best prognosis.